Fetal and Neonatal Levels of Omega-3: Effects on Neurodevelopment, Nutrition, and Growth - Juliana Rombaldi Bernardi; Renata de Souza Escobar; Charles Francisco Ferreira; Patrícia Pelufo Silveira (The Scientific World Journal)
Nutrition in pregnancy, during lactation, childhood, and later stages has a fundamental influence on overall development. There is a growing research interest on the role of key dietary nutrients in fetal health. Omega-3 polyunsaturated fatty acids (n-3 LCPUFAs) play an important role in brain development and function. Evidence from animal models of dietary n-3 LCPUFAs deficiency suggests that these fatty acids promote early brain development and regulate behavioral and neurochemical aspects related to mood disorders (stress responses, depression, and aggression and growth, memory, and cognitive functions). Preclinical and clinical studies suggest the role of n-3 LCPUFAs on neurodevelopment and growth. n-3 LCPUFAs may be an effective adjunctive factor for neural development, growth, and cognitive development, but further large-scale, well-controlled trials and preclinical studies are needed to examine its clinical mechanisms and possible benefits. The present paper discusses the use of n-3 LCPUFAs during different developmental stages and the investigation of different sources of consumption. The paper summarizes the role of n-3 LCPUFAs levels during critical periods and their effects on the children’s neurodevelopment, nutrition, and growth.